2017
DOI: 10.1080/10888438.2017.1318393
|View full text |Cite
|
Sign up to set email alerts
|

Reading Intervention for Poor Readers at the Transition to Secondary School

Abstract: This study evaluated two 20-week reading interventions for pupils entering secondary school with reading difficulties. The interventions were delivered by trained teaching assistants (three, 35-minute sessions per week). 287 pupils (aged 11-13) from 27 schools were randomly allocated to three groups; Reading Intervention (targeting word recognition and decoding skills), Reading Intervention plus Comprehension, or a waiting list control group. Neither intervention produced statistically significant gains in wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Hulslander et al, 2010). Indeed, promising intervention approaches have yielded modest improvements in reading comprehension for secondary pupils (Clarke, Paul, Smith, Snowling, & Hulme, 2017;Scammacca, Roberts, Figure 5. Final model with second-order language factor for each time point.…”
Section: Discussionmentioning
confidence: 99%
“…Hulslander et al, 2010). Indeed, promising intervention approaches have yielded modest improvements in reading comprehension for secondary pupils (Clarke, Paul, Smith, Snowling, & Hulme, 2017;Scammacca, Roberts, Figure 5. Final model with second-order language factor for each time point.…”
Section: Discussionmentioning
confidence: 99%
“…In one study (Haines et al, 2018), treatment group students performed significantly higher on a standardized reading measure at the 2-year follow-up compared with posttest. In contrast, the data from three studies showed that treatment group students performed significantly lower on certain reading measures at follow-up than at the immediate posttest (Clarke et al, 2017; Esser, 2001; Jitendra et al, 2000).…”
Section: Resultsmentioning
confidence: 96%
“…Participants in nine studies included in this synthesis were sixth, seventh, eighth, and/or ninth graders (Berkeley et al, 2011; Clarke et al, 2017; Esser, 2001; Haines et al, 2018; Jitendra et al, 2000; Lane, 1997; Newbern, 1998; O’Connor et al, 2019; Vachon, 1999). Participants in one study (Kennedy et al, 2015) were 10th graders.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluent readers are mentioned by increase in reading comprehension and general academic achievement and positive attitudes. On the other hand, reading difficulty is associated with failure in personal and academic tasks (Clarke, Smith, Paul, Snowling & Hulme, 2017;Dawes, Leitao, Claessen & Nayton, 2015;Mahapatra, 2016;Visser, 2014). Visser (2014) put forth deficits of poor readers in their temporal attention spans.…”
Section: Introductionmentioning
confidence: 99%